2018
DOI: 10.1111/jgh.13995
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of hepatitis C virus infection in a developing country: India

Abstract: Hepatitis C virus infection in northern India is seen more commonly in men, the middle aged and people from rural background and low to middle socioeconomic status. The common possible risk factors are dental treatment and exposure to reused syringes and needles. Although the most common presentation is incidental detection, a large number of patients present with advanced liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 43 publications
3
19
0
Order By: Relevance
“…Residence in a rural versus urban area was determined to be an effect modifier in our analysis. Individuals in rural areas of Punjab had 2.5 times the odds of being anti-HCV positive as those in urban settings after adjusting for covariates, a result comparable to other studies in North India[ 30 ]. Upon stratification, we found that sex, age and blood transfusions were associated with HCV among participants in rural areas, whereas in urban areas the only significant association was with age.…”
Section: Discussionsupporting
confidence: 79%
“…Residence in a rural versus urban area was determined to be an effect modifier in our analysis. Individuals in rural areas of Punjab had 2.5 times the odds of being anti-HCV positive as those in urban settings after adjusting for covariates, a result comparable to other studies in North India[ 30 ]. Upon stratification, we found that sex, age and blood transfusions were associated with HCV among participants in rural areas, whereas in urban areas the only significant association was with age.…”
Section: Discussionsupporting
confidence: 79%
“…Most of HCV infected individuals were of the middle‐aged group (33.10 years, SD ±19.55 years) as also observed in another Indian study . Patients infected with GT1a were younger (mean age, 12.69 ± 12.78 years) compared with patients infected with HCV GT3a (39.22 ± 16.76 years; P < 0.05).…”
Section: Discussionsupporting
confidence: 75%
“…Usage of unsterile needle injection by quacks was recorded in 19.05% of patients. Past history of surgery, dental intervention, unsterile needle usage, and use of unscreened blood/blood products for transfusion were commonly reported from different regions of India …”
Section: Discussionmentioning
confidence: 99%
“…The distribution of G1, G2, G3, G4, G5, G6 and mixed genotypes in Asia are iden-tified as 46.6%, 18.6%, 22.4%, 1.0%, 0.1%, 7.0% and 4.3% respectively. 7 In India, HCV prevalence has been estimated at 1-1.9% and as per the study in West Bengal, an increasing drift was found from children aged below 10 years (0.31%) to adults aged 60 years (1.85%); however, there is no significant difference observed between males and females. 5 Various efforts such as, active screening of high-risk groups for HCV infection, provision of safe blood and blood products, avoiding unsafe injection practices, adequate awareness and education and effective vaccination programs have been implemented in order to prevent HCV in India, which eventually reduced the overall prevalence of HCV in India.…”
Section: Hcv In Indian Contextmentioning
confidence: 87%